The productivity impact of R&D investment: evidence from European microdata - Raquel Ortega-Argilés; Lesley Potters; Marco Vivarelli (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The aim of this study is to investigate the relationship between a firm's R&D activities and its productivity using a unique micro data panel dataset and looking at sectoral peculiarities which may emerge; more specifically, we used an unbalanced longitudinal database consisting of 532 top European R&D investors over the six-year period 2000-2005. Our main findings can be summarised along the following lines: knowledge stock has a significant positive impact on a firm's productivity, with an overall elasticity of about 0.125; this general result is largely consistent with previous literature in terms of the sign, the significance and the estimated magnitude of the relevant coefficient. More interestingly, the coefficient increases monotonically when we move from the low-tech to the medium-high and high-tech sectors, ranging from a minimum of 0.05/0.07 to a maximum of 0.16/0.18. This outcome, in contrast with recently-renewed acceptance of low-tech sectors as a preferred target of R&D investment, suggests that firms in high-tech sectors are still far ahead in terms of the impact on productivity of their R&D investments, at least as regards top European R&D investors.
Keywords: O33; 330; R&D; productivity; knowledge stock; panel data; perpetual inventory method; Industrielle Forschung; Investition; Forschungskosten; Produktivität; Unternehmensentwicklung; Wissen; Panel; EU-Staaten